Mental Accounting, Access Motives, and Overinsurance - Markus Fels (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Consumers frequently overinsure modest risks. I argue that confining consumers' insurance motives to a single motive - risk aversion - is responsible for the difficulty to rationalize this behavior. People who perform mental accounting have an additional motive for buying insurance. They perceive a risk of having insufficient means to self-insure. This complements behavioral approaches to explain the profitability of warranties and the dislike of deductibles. It accounts for several empirical regularities that are difficult to reconcile within existing models. Finally, it suggests that the way in which an insurer pays benefits influences the value and the cost of insurance.
Keywords: D11; D14; D81; 330